SEO ANALYSIS FOR ENHANCING AUDIENCE ENGAGEMENT ON ADAINFO.OFFICIAL YOUTUBE CONTENT - M Rifqi Imam Sabillah; Diva Aulia Ananta; Badriyah (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
YouTube is one of the digital streaming platforms with the largest user base in the world. This makes it one of the most effective digital media platforms for distributing information. However, with the large number of creators today, competition has become increasingly fierce, making Search Engine Optimization (SEO) a key strategy for boosting the visibility of video content. This study was conducted to determine the extent to which the implementation of SEO affects the performance and engagement of the YouTube video content on the Adainfo.Official channel. A quantitative descriptive method was used in this study, employing a pre-experimental design of the One-Group Pretest-Posttest type and a case study approach. Direct observation using YouTube Analytics was used to collect data, and purposive sampling was applied to three video samples before and after SEO implementation. The indicators analyzed were impressions, views, CTR, and engagement rate. The results indicate that SEO strategies improve several video content performance metrics. Impressions increased by 240.6%, views increased by 503.1%, and CTR increased by 206.3%. However, there was a 93.4% decrease in the Engagement Rate (ER) indicator. This indicates that the results of SEO implementation have a positive impact on improving the visibility and reach of video content, but have not yet had a significant effect on increasing audience engagement.